2020
DOI: 10.1186/s40798-020-00270-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exercise-Induced Fatigue on Inter-Limb Asymmetries: a Systematic Review

Abstract: Background Non-contact injuries such as anterior cruciate ligament ruptures often occur during physical load toward the end of a match. This is ascribed to emerging processes due to exercise-induced fatigue. Moreover, non-contact injuries often occur during dynamic actions such as landing or cutting movements. Inter-limb asymmetries are suggested as one possible cause for those injuries based on findings indicating that asymmetries between limbs are associated with a higher injury risk. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 66 publications
1
56
0
Order By: Relevance
“…Recent results of Wei et al (2017) further revealed that gait asymmetry is an important factor for the prediction of falls in stroke patients 68 . Also of note is that chronic gait asymmetry could also lead to increased risk of lower-limb overuse injuries and articular joint degeneration due to the increased weight bearing and propulsion demands placed on one lower limb during walking, in both pathological 69 – 72 and healthy populations 73 . Along these lines, gait asymmetry can be used as (i) a metric to assess pathology status, patients’ functional recovery or disease progression, (ii) a target for interventions aiming to improve gait performance, and (iii) outcome to evaluate and compare different gait rehabilitation programs interventions 43 , 55 , 74 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent results of Wei et al (2017) further revealed that gait asymmetry is an important factor for the prediction of falls in stroke patients 68 . Also of note is that chronic gait asymmetry could also lead to increased risk of lower-limb overuse injuries and articular joint degeneration due to the increased weight bearing and propulsion demands placed on one lower limb during walking, in both pathological 69 – 72 and healthy populations 73 . Along these lines, gait asymmetry can be used as (i) a metric to assess pathology status, patients’ functional recovery or disease progression, (ii) a target for interventions aiming to improve gait performance, and (iii) outcome to evaluate and compare different gait rehabilitation programs interventions 43 , 55 , 74 77 .…”
Section: Discussionmentioning
confidence: 99%
“…However, all the subjects with a side-difference greater than 4 cm had composite scores under 94% post-load, indicating an especially high potential injury risk for these subjects. In future work, given inter-individual variation and task-specificity of side-differences, a more individual approach seems advisable [33,49]. Nevertheless, the prediction of the likelihood of injuries using the YBT has recently been doubted [50], and the particular YBT is not able to give an overall impression of all types of dynamic postural control.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Wright et al [20] found a negative effect after running but not after cycling, suggesting that the results may additionally depend on the type of load and the induced type of fatigue (whole body vs. local) [20]. This loading protocol specificity should also be considered during future studies [29] and the used tasks and protocols should try to mimic the sport-specific demands [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations